Preoperative Concurrent Chemoradiotherapy Versus Neoadjuvant Chemotherapy for Locally Advanced Gastric Cancer: Phase II Randomized Study - Wang, Xin; Zhao, Dong-Bing; Yang, Lin; Chi, Yihebali; Zhao, Hong; Jiang, Li-Ming; Jiang, Jun; Tang, Yuan; Li, Ning; Liu, Wen-Yang; Dou, Li-Zhou; Zou, Shuang-Mei; et al. (Frontiers in Oncology, 2022)
Objective We evaluated and compared the efficacy and safety of neoadjuvant chemoradiotherapy (NACRT) versus neoadjuvant chemotherapy (NACT) for locally advanced gastric cancer (LAGC) in a single-center randomized phase II trial. Methods Patients with LAGC were enrolled and received either NACT or NACRT, followed by gastrectomy and adjuvant chemotherapy. The primary endpoint was an R0 resection rate. Results We enrolled 75 patients: 75.7% (NACT, 28/37 patients) and 76.3% (NACRT, 29/38 patients) underwent surgery; R0 resection rates were 73.0% (27/37) and 73.7% (28/38), respectively. The NACRT group had significantly better major pathological response than the NACT group (37.9% vs 17.9%, p = 0.019). Between-group postoperative complications were not significantly different. The median follow-up was 59.6 months; 5-year overall survival (OS) rate was 50.1% (NACT) and 61.9% (NACRT); neither group reached the median OS; median progression-free survival was 37.3 and 63.4 months, respectively. Conclusions S-1-based NACRT did not improve the R0 resection rate, although it presented better tumor regression with similar safety to NACT. Trial registration ClinicalTrial.gov NCT02301481